Program Penanganan Tanggap Darurat dan Pemulihan Pasca Banjir di Kabupaten Nagan Raya - Apri Rotin Djusfi; Fiandy Mauliansyah; Yuliatul Muslimah; Irsadi Aristora; Iwan Doa Sampena; Muffaruddin Muffaruddin (Universitas Teuku Umar, 2026)
The flood disaster that occurred at the end of 2025 in Nagan Raya Regency, Aceh Province, had a significant impact on the fulfillment of basic needs in rural communities, particularly in relation to housing conditions, access to clean water, environmental health, and socio-economic activities. Such emergency conditions require a rapid, coordinated, and needs-based response. This article aims to describe the implementation of a Disaster Emergency Community Service Program conducted by Universitas Teuku Umar with funding support from the Directorate of Research and Community Service, Ministry of Higher Education, Science, and Technology. The community service activities were carried out in Drien Tujoh Village, Tripa Makmur District, as well as Blang Meurandeh, Kuta Tengoh, Blang Puuk, and Babah Suak Villages in Beutong Ateuh Banggalang District. The implementation employed a rapid response approach based on field needs, encompassing needs assessment, coordination with village authorities, procurement of aid, and direct distribution to affected communities. The assistance provided included food logistics, basic household necessities, and emergency-support technologies such as generators, water pumps, clean water distribution facilities, and field communication devices. The results indicate that the program contributed positively to meeting basic community needs during the emergency response phase and early post-disaster recovery. The distribution of aid and supporting technologies helped maintain access to clean water, support the continuity of social activities, and strengthen the capacity of village institutions in coordinating disaster response efforts. This program highlights the strategic role of higher education institutions in disaster management through a collaborative, responsive, and context-based approach. The program outputs include increased community empowerment, mass media publications, impact videos, and a scholarly article published in a community service journal.